Codoped Tb3+ and Mn2+ induced tunable emission and energy transfer in Ca19Zn2(PO4)14:Ce3+, Tb3+, Mn2+. (18th September 2018) - Liang, Chao; Fu, Yibing; Teng, Xiaoming; Liu, Kai; You, Hongpeng; He, Jinhua
Abstract : By tuning the relative content of the doped ions, tunable blue-green emission can be obtained. Abstract : To explore a new phosphor, Ca19 Zn2 (PO4 )14 :Ce 3+, Tb 3+ and Ca19 Zn2 (PO4 )14 :Ce 3+, Mn 2+ phosphors are successfully synthesized with the objective of application in ultraviolet-based light-emitting diodes. X-ray diffraction (XRD), photoluminescence (PL) spectra, and lifetimes were used to characterize the samples. Under UV excitation, the energy transfer from the Ce 3+ to Tb 3+ ions in the Ca19 Zn2 (PO4 )14 host occurred mainly via a dipole–quadrupole mechanism, and the critical distances of the ion pairs ( R C ) were calculated by the spectral overlap method. A bright red light emission was observed in the Ce 3+ and Mn 2+ codoped samples via the energy transfer from the sensitizer Ce 3+ to Mn 2+ ions. With an appropriate ratio of the active ion concentrations, the Ce 3+, Tb 3+ and Ce 3+, Mn 2+ codoped Ca19 Zn2 (PO4 )14 phosphors can generate light from the blue to green and blue to orange regions, respectively. The emission colors of the phosphors were also clarified by CIE coordinates briefly.